Korrespondenzen. - Gohr, Siegfried (Köln : Michael Werner, 1992)
Dürer, Albrecht ; Rodin, Auguste ; Immendorff, Jörg ; Giacometti, Alberto ; Baselitz, Georg ; Penck, A.R. ; Lüpertz, Markus ; Derain, André ; Beckmann, Max ; Baselitz, Georg
Korrespondenzen, Michael Werner, Köln, 10. April bis 20. Mai 1992
boek